"Route CZ-AT" to the USA: Perceiving American Culture in Central Europe - et, al (Univerzita Palackého v Olomouci, 2018)
While English is the lingua franca and an established language in numerous countries, it is its American variant that keeps spreading rapidly to other parts of the world due to the wide ranging influence of the USA in politics, economics and popular culture. The nine authors of this volume present various aspects associated with the perception of the USA, whether it be American English, a theme in American literature and culture or an analysis of their reception in and/or influence on the Czech Republic or Austria.
Keywords: Lingvistika